Ferroptosis, oxidative stress and hearing loss: Mechanistic insights and therapeutic opportunities - Chenyang Yuan; Tianyu Ma; Mengting Liu; Xiaoyun Zeng; Gongrui Tang; Yazhi Xing; Tianhong Zhang (Heliyon)
Hearing loss, a prevalent sensory impairment, poses significant challenges worldwide. Recent research has shed light on the intricate interplay between ferroptosis, a newly recognized form of regulated cell death characterized by iron-dependent lipid peroxidation, and oxidative stress in the pathogenesis of hearing loss. In this review, we delve into the mechanisms underlying ferroptosis and oxidative stress in various forms of hearing loss, including age-related hearing loss (ARHL), noise-induced hearing loss (NIHL) ototoxic drug-induced hearing loss and genetic hearing loss. We discuss the pivotal role of molecules such as FSP1, ACSL4, LKB1-AMPK, and Nrf2 in modulating these pathways in hearing loss. Furthermore, we explore emerging therapeutic strategies targeting the antioxidant system and ferroptosis, including iron chelators, lipid peroxide inhibitors, and antioxidants, highlighting their potential in mitigating hearing loss progression. By elucidating the molecular mechanisms underlying ferroptosis and oxidative stress, this review offers insights into novel therapeutic avenues for the treatment of hearing loss and underscores the importance of targeting these pathways to preserve auditory function.